Cardiorenal outcomes after herpes zoster reactivation in COVID-19 survivors from a global TriNetX study - Chien-Lin Lu; Joshua Wang; Ya-Chieh Chang; Kuo-Cheng Lu (Scientific Reports)
Abstract Herpes zoster (HZ) has emerged as a post-viral complication in COVID-19 survivors, but its long-term clinical impact remains uncertain. This retrospective cohort study utilized the TriNetX Global Collaborative Network to evaluate whether HZ reactivation after COVID-19 is associated with increased risks of mortality, cardiovascular, and renal outcomes. Adults diagnosed with HZ within one year of COVID-19 were propensity score–matched 1:1 with controls without HZ. A total of 48,442 matched patients were followed for three years. Compared with controls, HZ patients had significantly higher risks of major adverse cardiovascular events (HR: 1.38, 95% CI: 1.30–1.46), acute kidney injury (HR: 1.67, 95% CI: 1.55–1.80), and renal function decline defined by eGFR < 60 mL/min/1.73 m² (HR: 1.28, 95% CI: 1.20–1.37). Although no significant difference in overall all-cause mortality was observed across the full follow-up period, time-stratified analysis revealed a biphasic pattern: patients with HZ had lower mortality risk during the first 90 days but showed significantly higher mortality from day 91 to three years post-COVID-19 (HR: 1.33, 95% CI: 1.24–1.44). Subgroup analyses consistently identified older age, chronic comorbidities, impaired renal function, and systemic inflammation as risk enhancers across outcomes. These findings suggest that HZ reactivation after COVID-19 signals a vulnerable subgroup predisposed to cardiorenal complications. Targeted follow-up and risk-based interventions are warranted in this population.